METHODOLOGICAL FOUNDATIONS OF BUILDING A MODEL OF INTERACTION OF MARKETING TOOLS - Kozak, KATERYNA; Bakay, ROMAN (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the methodological foundations for developing an effective set of enterprise marketing tools. It has been established that constructing such a system requires a phased application of appropriate tools, depending on the purpose, subject, and marketing research methods. It is substantiated that marketing tools, as an integral part of the closed management cycle, ensure the adaptability and flexibility of the enterprise's marketing system. A structural classification of marketing tools is proposed according to the following areas: external market research, internal environment analysis, marketing mix formation, and evaluation of decision-making effectiveness. The paper examines and characterizes marketing instruments used at the specified stages of the marketing cycle. It is noted that modern digital marketing tools, despite their specific nature, remain a logical extension of the traditional marketing mix.Effective marketing management should be based on a holistic management model encompassing planning, organization, motivation, and control, with consideration of the integration of analytical, communicative, and strategic elements in a dynamic market environment. Such an approach contributes to achieving both strategic and tactical goals, enhancing enterprise competitiveness and resilience. The key elements of adaptive management are continuous updating of the analytical base, market monitoring, digital technology implementation, and preventive strategies.The article also examines modern approaches to assessing the effectiveness of marketing decision-making in the context of enterprise performance in a dynamic market environment. The necessity of clarifying the conceptual framework and defining effectiveness as the degree of alignment between implemented marketing actions and the enterprise’s strategic goals is substantiated. A systematic approach to marketing performance evaluation is proposed, involving process structuring by key directions: analytics, segmentation, sales, functional organization, and management quality. It is concluded that the integrated application of these methods enables the identification of marketing strategy outcomes and the development of well-grounded managerial decisions tailored to the conditions of economic instability, institutional transformations, and globalization processes.
Keywords: marketing tools; marketing mix; market research; enterprise research; marketing performance; marketing cycle; management model